Design Control and Monitoring System using the Fuzzy Mamdani Method on IoT-Based Air Conditioner - Wulan Nursyifa Rumbaman; Lukman Medriavin Silalahi; Cian Ramadhona Hassolthine; Vika Febri Muliati; Fesa Asy Syifa Nurul Haq (Universitas Telkom, 2024)
The development of Air Conditioner technology to stabilize the temperature and humidity of the air in a room has affected human life activities. This research designed an automatic control system for air conditioning using the Fuzzy Mamdani method, because it is known that air conditioners have the largest cost burden compared to other electronic devices. Then, this research designed a control system consisting of a DHT22 Sensor as an input to detect the room temperature controlled by the ESP32. Furthermore, the results of data collection are analyzed using the Fuzzy Mamdani method so that the defuzzification output instructs the relay to take action, namely switching off to adjust the temperature degree and display data to the IoT platform, ThingSpeak. The results of this research show that the DHT22 sensor test was successfully calibrated with a hygrometer comparator with an error value of 0.4%. Then, the prototype design based on fuzzy rules has been successfully implemented with an error value of 9.2% from the manual comparison so that it is concluded that the deviation difference is still recommended. This indicates that the system effectively maintains desired environmental conditions while improving energy efficiency by reducing unnecessary AC usage. The results confirm the feasibility of implementing IoT-based fuzzy control systems for practical energy-saving applications.